The Relationship Between Academic Achievement And Students General Health And Coping Styles: A Study on Nursing Midwifery And Health Students of Islamic Azad University - Kerman Branch - Maryam Zeighami; Narjes Pour Bahaadini Zarandi (Kerman University of Medical Sciences, 2011)
Background & Objective: The development of each community is highly dependent on its educated individuals Therefore recognition of factors influencing academic achievement of students and attention to these factors are essential for success T he aim of the present study was to determine the relationship between academic achievement and two factors of general health and coping styles among undergraduate students Methods: In this descriptive crosssectional study 302 Nursing Midwifery and Health students of Kerman Azad University were studied Grade point average was considered as an indicator of academic achievement and all participants were asked to complete Goldberg general health questionnaire (GHQ28) and Endler ;Parker questionnaire of coping inventory for stressful situation (CISS) Results: The Most Frequent average total score was 141699 (out of 20) In 633% of students total score of General Health was not in the normal range Students used taskoriented coping style more frequently than other styles (% 49)There was a significant negative relationship between academic achievement and two studied factors of general health and emotionoriented coping style Conclusion: Since general health and copying style can have significant effects on students academic achievement the presence of active counseling centers in universities for improving general health level of students and teaching effective copying styles is highly necessary